THE PARADIGM OF MULTICULTURAL EDUCATION THROUGH DEVELOPMENT OF UNITY IN DIVERSITY - Suprihno Suprihno (LP2M IAIN Tulungagung, 2019)
Abstract: This article is analysing the paradigm of Multicultural Education trough development of character unity in diversity. Multicultural education is an alternative to solve the problem of the diversity in Indonesia. Diversity in negative meaning has spawned suffering long time for human beings. At this time, at least there have been 35 major conflicts between ethnic groups in the world. More than 38 million inhabitants driven out of the place that they live, at least a bit of 7 million people has been killed in the conflict ethnic bloody. A long Conflict involves sentiments of ethnic, racial, class and religion. This article using library research method. Sources of data used by researchers in accordance with the type of research that is literary or library research (library research) then in the form of literature from books, documents, journals or scientific papers. Nation Indonesia is needed of unity, things have to be formed if done by the principle of unity in diversity. To foster a tradition of unity in diversity, multicultural education is needed. Multicultural education is a bridge to usher in a new generation of open faces of difference, the development of a nation's culture that is farthest from prejudice, conflict and violence. Eliminating sectarian views and exclusivity. And will open the view inclusivity open to cooperation with other people, despite having beliefs, opinions, identity and different style of life. One of the forms of problem solving is transforming the program called “service learning”. There is a method of learning. In which students learn and develop their competence by way of actively participating in the practice of the service of society is organized. Keyword: Education, Multicultural, unity in diversity, Service-learning